Phenotypic and spatial heterogeneity of brain myeloid cells after stroke is associated with cell ontogeny, tissue damage, and brain connectivity - Anirudh Patir; Jack Barrington; Stefan Szymkowiak; Gaia Brezzo; Dana Straus; Alessio Alfieri; Lucas Lefevre; Zhaoyuan Liu; Florent Ginhoux; Neil C. Henderson; Karen Horsburgh; Prakash Ramachandran; et al. (Cell Reports, 2024)
Summary: Acute stroke triggers extensive changes to myeloid immune cell populations in the brain that may be targets for limiting brain damage and enhancing repair. Immunomodulatory approaches will be most effective with precise manipulation of discrete myeloid cell phenotypes in time and space. Here, we investigate how stroke alters mononuclear myeloid cell composition and phenotypes at single-cell resolution and key spatial patterns. Our results show that multiple reactive microglial states and monocyte-derived populations contribute to an extensive myeloid cell repertoire in post-stroke brains. We identify important overlaps and distinctions among different cell types/states that involve ontogeny- and spatial-related properties. Notably, brain connectivity with infarcted tissue underpins the pattern of local and remote altered cell accumulation and reactivity. Our discoveries suggest a global but anatomically governed brain myeloid cell response to stroke that comprises diverse phenotypes arising through intrinsic cell ontogeny factors interacting with exposure to spatially organized brain damage and neuro-axonal cues.